STAGES OF DEVELOPMENT OF STATE AND NON-STATE PRESCHOOL EDUCATIONAL ORGANIZATIONS (Archive of Conferences, 2022)
This article examines the level of development and processes of public and non-governmental preschool education, and reveals its theoretical and scientific significance. The physical, moral, aesthetic, and physiological development of a preschool organization takes place.